Academic attainment and special educational needs in extremely preterm children at 11 years of age: the EPICure study. Issue 4 (12th March 2009) - Johnson, S; Hennessy, E; Smith, R; Trikic, R; Wolke, D; Marlow, N
Abstract : Aim: To assess academic attainment and special educational needs (SEN) in extremely preterm children in middle childhood. Methods: Of 307 extremely preterm (⩽25 weeks) survivors born in the UK and Ireland in 1995, 219 (71%) were re-assessed at 11 years of age and compared to 153 classmates born at term, using standardised tests of cognitive ability and academic attainment and teacher reports of school performance and SEN. Multiple imputation was used to correct for selective dropout. Results: Extremely preterm children had significantly lower scores than classmates for cognitive ability (−20 points; 95% CI −23 to −17), reading (−18 points; −22 to −15) and mathematics (−27 points; −31 to −23). Twenty nine (13%) extremely preterm children attended special school. In mainstream schools, 105 (57%) extremely preterm children had SEN (OR 10; 6 to 18) and 103 (55%) required SEN resource provision (OR 10; 6 to 18). Teachers rated 50% of extremely preterm children as having below average attainment compared with 5% of classmates (OR 18; 8 to 41). Extremely preterm children who entered compulsory education an academic year early due to preterm birth had similar academic attainment but required more SEN support (OR 2; 1.0 to 3.6). Conclusions: Extremely preterm survivors remain at high risk for learning impairments and poor academic attainment in middle childhood. A significant proportion require full-time specialist education and over half of those attending mainstream schools require additional health or educational resources to access the national curriculum. The prevalence and impact of SEN are likely to increase as these children approach the transition to secondary school.